Effectiveness of Structural Couple Therapy and Intensive Short-Term Dynamic Psychotherapy on Intrapersonal-Interpersonal Skills and Family Function in Couples - Nayereh Sadat Sadatmand; Ozra Etemadi; Fatemeh Bahrami; Maryam Fatehizadeh (Iranian Evolutionary Educational Psychology Journal)
Objective: The current investigation sought to evaluate the efficacy of structural couple therapy in conjunction with Intensive Short-Term Dynamic Psychotherapy (ISTDP) regarding the enhancement of intrapersonal-interpersonal skills and family function of couples. Methods: The research methodology employed was a quasi-experimental design incorporating pre-test and post-test assessments alongside a control group. The statistical population comprised couples who sought assistance at counseling centers within Tehran and who exhibited difficulties in performance, intrapersonal, and interpersonal competencies. A total of 24 couples were selected through convenience sampling and subsequently allocated at random to two experimental groups and one control group, with each group containing eight couples. The two experimental cohorts underwent six treatment interventions distributed over a total of twelve sessions. The instruments utilized in this study encompassed the Family Assessment Device (FAD-I), Intrapersonal-Interpersonal Skills Couple Scale (IISCS), and clinical interviews. Analysis of covariance alongside the LSD test was employed to facilitate comparisons of mean scores among the groups. Results: The findings indicated the significant effectiveness of both structural couple therapy and ISTDP in enhancing couples' performance as well as their intrapersonal and interpersonal skills. Nevertheless, no statistically significant differences were detected between the two experimental groups. The results unequivocally demonstrated that intrapersonal skills experienced enhancement within the ISTDP group, whereas improvements in interpersonal skills were observed within the structural group (P<0.001). Conclusions: In light of the findings, it is recommended that integrated methodologies that concurrently incorporate both intrapersonal and interpersonal dimensions be adopted in interventions targeting couples.